1996
DOI: 10.1002/(sici)1097-0215(19960301)65:5<671::aid-ijc18>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a small-cell-lung-carcinoma cell line from a patient with cancer-associated retinopathy

Abstract: We examined the biologic properties of a small-cell-lungcarcinoma (SCLC) cell line (designated MN-I I 12) established from a patient with SCLC who showed paraneoplastic retinopathy syndrome. Morphologic and immunocytochemical analyses showed that MN-I I I2 cells possess features of the classic type of SCLC. MN-I I I 2 cells grew in suspension forming relatively large clumps of cells with a doubling time of 72 hr. By light-microscope examination, the cells were relatively small and had scanty cytoplasm. The cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…As a mechanism for the apoptotic cell death of photoreceptor cells observed in CAR, it has been postulated that anti-recoverin antibody generated by unknown mechanisms in some cancer patients penetrates into the photoreceptor cells via the peripheral circulation and causes misregulation of the phototransduction pathway by blocking recoverin function (Adamus et al 1998;Maeda et al 2001b). In the initial step of CAR pathogenesis, several studies suggested that aberrant expression of retina-specific recoverin, serving as a shared antigen between tumor cells and retina, was critical since such aberrant expression of recoverin had been identified in tumor cells in CAR patients but not in non-CAR cancerous patients (Polans et al 1995;Matsubara et al 1996;Yamaji et al 1996). However, in contrast, we have recently found that aberrant expression of retina-specific recoverin occurred in more than 50% of several kinds of cancer cells, and their cell lines obtained from non-CAR cancerous patients (Maeda et al 2000;Maeda et al 2001a).…”
Section: © 2004 Tohoku University Medical Presssupporting
confidence: 85%
“…As a mechanism for the apoptotic cell death of photoreceptor cells observed in CAR, it has been postulated that anti-recoverin antibody generated by unknown mechanisms in some cancer patients penetrates into the photoreceptor cells via the peripheral circulation and causes misregulation of the phototransduction pathway by blocking recoverin function (Adamus et al 1998;Maeda et al 2001b). In the initial step of CAR pathogenesis, several studies suggested that aberrant expression of retina-specific recoverin, serving as a shared antigen between tumor cells and retina, was critical since such aberrant expression of recoverin had been identified in tumor cells in CAR patients but not in non-CAR cancerous patients (Polans et al 1995;Matsubara et al 1996;Yamaji et al 1996). However, in contrast, we have recently found that aberrant expression of retina-specific recoverin occurred in more than 50% of several kinds of cancer cells, and their cell lines obtained from non-CAR cancerous patients (Maeda et al 2000;Maeda et al 2001a).…”
Section: © 2004 Tohoku University Medical Presssupporting
confidence: 85%
“…Thirkill et al (1993) previously suggested that recoverin expression could be induced in otherwise quiescent SCLC cell lines. However, the expression of recoverin in an SCLC cell line, MN-1112, was not induced during the establishment and passage of the cell line because, as previously reported, the recoverin expression was immunohistochemically demonstrated in a primary SCLC tumour of the CAR patient from which the cell line was derived (Matsubara et al, 1996).…”
Section: Discussionmentioning
confidence: 58%
“…An SCLC cell line, designated MN-1112, was established from a tumour of an SCLC patient with CAR (Yamaji et al, 1996). The patient profile had been described previously (Matsubara et al, 1996).…”
Section: Cell Linesmentioning
confidence: 99%
“…This protein is a member of the E-F hand family of calcium-binding proteins involved in the transduction of light by vertebrate photoreceptors and is also identified as an autoantigen in CAR (12,13). It has been reported that this photoreceptor-specific protein is expressed by the tumor in CARpatients (16) and by a human lung cancer cell line (MN-1112), which was established from tumors of small-cell lung carcinoma patients with CAR (17,26). In addition, expression of recoverin was not found in patients with diabetic retinopathy, age-related macular degeneration and in small-cell lung carcinoma patients without CAR (7,17).…”
Section: Discussionmentioning
confidence: 99%